Realistic efficiency potential of next‐generation industrial Czochralski‐grown silicon solar cells after deactivation of the boron–oxygen‐related defect center. (18th January 2016) - Walter, Dominic C.; Lim, Bianca; Schmidt, Jan
Abstract: We measure carrier lifetimes of different Czochralski‐grown silicon (Cz‐Si) materials of various boron and oxygen concentrations and determine the maximum achievable lifetime after an optimized thermal treatment. We obtain very high and stable bulk lifetimes of several milliseconds, virtually eliminating the boron–oxygen (BO) defect complex, which previously limited the carrier lifetime in boron‐doped Cz‐Si materials after prolonged illumination. Based on these experimental results, we introduce a new parameterization of the bulk lifetime of B‐doped Cz‐Si after permanent deactivation of the BO center. Notably, we measure lifetimes up to 4 ms on 2‐Ωcm Cz‐Si wafers at an injection level of 1/10 of the doping concentration. Importantly, these high lifetime values can be reached within 10 and 20 s of BO deactivation treatment. A detailed analysis of the injection‐dependent lifetimes reveals that the lifetimes after permanent deactivation of the BO center can be well described by a single‐level recombination center characterized by an electron‐to‐hole capture cross‐section ratio of 12 and located in the middle of the silicon band gap. We implement the novel parameterization into a two‐dimensional device simulation of a passivated emitter and rear solar cell using technologically realistic cell parameters. The simulation reveals that based on current state‐of‐the‐art solar cell production technology, efficiencies reaching 22.1% are realistically achievable in the near future after complete deactivation of the BO center. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : High carrier lifetimes in Czochralski‐grown silicon, up to 4 ms on 2‐Ωcm Czochralski‐grown silicon wafers, are achievable after deactivation of the boron‐oxygen (BO)‐related defect center and an optimized thermal treatment. A new parameterization of the lifetime after deactivation of the BO center depending on the base doping concentration is presented. Conversion efficiencies exceeding 22% are realistically achievable in the near future after complete deactivation of the BO center.